Analysis of alkyl esters of p-hydroxybenzoic acid (parabens) in baby teethers via gas chromatography-quadrupole mass spectrometry (GC-qMS) using a stable isotope dilution assay (SIDA). Issue 17 (14th April 2016) - Potouridis, Theodoros; Berger, Elisabeth; Püttmann, Wilhelm
Abstract : The present work describes an analytical method for the analysis of methyl-, ethyl- and n -propylparaben in plastic and gel material from baby teethers filled with cooling gel. Abstract : Alkyl esters of p -hydroxybenzoic acid (parabens) are well-known to be used as preservatives in pharmaceuticals, cosmetics, and food products due to their antimicrobial effect. However, parabens are also known to act as endocrine disruptors. Thus, if manufactures of consumer goods use parabens particularly in products for infants and young children, this application should be considered as critical and should be thoroughly investigated, at least if an intake into the body cannot be excluded. The present work describes an analytical method for the analysis of methyl-, ethyl- and n -propylparaben (MeP, EtP and n -PrP) in plastic and gel material from baby teethers filled with cooling gel. Measurements were performed with gas chromatography-quadrupole mass spectrometry (GC-qMS) on N, O -bis(trimethylsilyl)trifluoroacetamide (BSTFA) derivatized parabens. Samples were prepared applying ultrasonic assisted extraction (UAE) using methanol as the solvent. For quantification, a stable isotope dilution assay (SIDA) was used that showed good recoveries for spiked gel material, which ranged from 82 to 119%. The baby teether analyses showed that parabens were present in all considered plastic and gel samples. Furthermore, in all gel samples (2 E, 4 E )-hexa-2, 4-dienoic acid (sorbic acid) was identified as an additional preservative.